Penerapan Model Pembelajaran Active Learning dalam Meningkatkan Aktivitas dan Hasil Belajar Biologi Siswa Kelas VIII - Ariati, Zulhia; Hirliana, Norma (Biocaster : Jurnal Kajian Biologi, 2024)
This research aims to determine the increase in student activity and learning outcomes through the application of the Active Learning learning model in biology lessons for class VIII students at SMP Negeri 12 Tasikmalaya. This type of research is Classroom Action Research (PTK). This research was conducted at SMP Negeri 12 Tasikmalaya. The population in this study were all class VIII students, while the sample used was 25 students. The instruments used in this research were observation sheets and test questions. Data collection techniques use observation and tests. The data analysis technique in this research is qualitative and quantitative data analysis. Qualitative data analysis is used to analyze data obtained from observations carried out in the first cycle and subsequent cycles, the data is collected and then concluded. Meanwhile, quantitative data analysis is used to process data in the form of numbers, both observation data and student learning outcomes (evaluation) data which are then processed into quantitative data in research. The results of this research show that, in cycle I, the student activity score was 2.5 in the quite active category and in cycle II it was 3.33 in the active category. For learning outcomes, the percentage of classical completeness in cycle I was 68% in the incomplete category and in cycle II it was 88% in the completed category. Thus it can be concluded that the application of the Active Learning learning model can improve the activities and learning outcomes of class VIII students at SMP Negeri 12 Tasikmalaya.